Analysis of DNA cox1 barcoding revealed novel haplotype in Schistosoma haematobium isolated from Western Sudan - Ishraga Adam Elzain; Abeer Babiker Idris; Abdul Aziz Karim; Nagla Mohamed Ahmed; Salaheldein G. Elzaki; Semih Yılmaz; Mohamed A. Hassan; Hamid Suliman Abdalla (Scientific Reports)
Abstract Schistosomiasis poses a significant global health threat, particularly in tropical and subtropical regions like Sudan. Although numerous epidemiological studies have examined schistosomiasis in Sudan, the genetic diversity of Schistosoma haematobium populations, specifically through analysis of the mtcox1 gene, remains unexplored. This study aimed to investigate the risk factors associated with urogenital schistosomiasis among school pupils in El-Fasher, Western Sudan, as well as the mtcox1 genetic diversity of human S. haematobium in this region. A cross-sectional study was conducted among school pupils aged 4 to 19 years. In total, 196 urine samples and 196 fecal samples were collected from participants across schools, health centers, and refugee camps in El-Fasher. Samples were examined using simple centrifugation/sedimentation technique and formol-ether concentration method to detect S. haematobium and S. mansoni eggs, respectively. S. haematobium mtcox1 partial gene was amplified and sequenced by the Sanger technique. A neighbor-joining phylogenetic tree was generated by MEGA software, and a haplotype network was constructed using PopART v.1.7 with the median-joining network method. In this study, S. haematobium was detected in 6.1% (12/196) of the participants while no S. mansoni ova were observed in fecal samples. The infection was more common among those who relied on indirect water supply like tankers (6, 50%). No infection was observed among residents of refugee camps. Only eight samples were PCR-positive, which were successfully sequenced, and included in the genetic diversity analysis. A unique haplotype (Hap_1) with no sequence diversity was found among cox1 sequences from El-Fasher strains. Both El-Fasher S. haematobium haplotype (Hap_1) and Gezira haplotype (Hap_31) fall within the mainland Africa group (group 1). In conclusion, this study identified a novel S. haematobium strain and provides insights into the evolutionary history and phylogeography of S. haematobium in Sudan, particularly in the western region. This genetic data could help in the control and monitoring of urogenital schistosomiasis in this region. For the first time, we utilized the DNA mtcox1 barcoding to investigate S. haematobium haplotypes in Western Sudan.